1989
DOI: 10.3109/17453678909150103
|View full text |Cite
|
Sign up to set email alerts
|

Hip motion related to age and sex

Abstract: In a selected population 4 years old to adult age, 1,522 hips in 761 healthy subjects of both sexes were studied. Arcs of passive motion of the hip were measured by the technique recommended by the American Academy of Orthopaedic Surgeons. The lower and upper limits of normal range of hip motion in all the planes were established for both sexes in the different age groups. We found that the amplitude of most hip motions decreased with age. Females had higher ranges of total hip motion, total rotation, internal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(44 citation statements)
references
References 14 publications
4
38
2
Order By: Relevance
“…Normal healthy hips have a mean 133°flexion, 19°T P-values were calculated by independent-samples t-test, except male/ female ratio and surgical approach; these were calculated by chisquare (Fisher's exact) tests All values given as mean and standard deviation (SD). P-values were calculated by paired-samples t-tests and refer to the difference between the preoperative and postoperative values extension, 40°abduction, 30°adduction, 41°internal endorotation and 39°external rotation [13]. It is suggested that ROM after THA should be 120°flexion, 20°abduction and 20°external rotation [14].…”
Section: Discussionmentioning
confidence: 99%
“…Normal healthy hips have a mean 133°flexion, 19°T P-values were calculated by independent-samples t-test, except male/ female ratio and surgical approach; these were calculated by chisquare (Fisher's exact) tests All values given as mean and standard deviation (SD). P-values were calculated by paired-samples t-tests and refer to the difference between the preoperative and postoperative values extension, 40°abduction, 30°adduction, 41°internal endorotation and 39°external rotation [13]. It is suggested that ROM after THA should be 120°flexion, 20°abduction and 20°external rotation [14].…”
Section: Discussionmentioning
confidence: 99%
“…31 With a sample size of 32 participants, we had 60% to 85% power to detect an R 2 value of 0.25 (considered a large effect), 31 depending on the number of variables that remained in the model (from 4 to 1, respectively). 30 Because GJL, 2,24 HIER ROM , 17,21 and measures of knee laxity 2,24 differ by sex, we also examined these associations within each sex. Significance was determined at P .05 by using a 1-tailed test (assuming associations would be positive in nature).…”
Section: Discussionmentioning
confidence: 99%
“…17,21 The pelvis was stabilized against the table to ensure that motion was limited to the hip joint. With an inclinometer (Universal Inclinometer; Performance Attainment Associates, Saint Paul, MN) attached along the long axis of the tibia, the tibia was positioned perpendicularly to the table to establish an initial zero position, as confirmed by the inclinometer's vertical zero reference position.…”
Section: Clinical Measurement Proceduresmentioning
confidence: 99%
“…4,7,17,28,34,44,48 In subjects without hip joint pathology, passive hip joint range of motion, for a specific motion like hip internal rotation, has consistently been shown to be symmetrical from the left to right side. [44][45][46] The normal discrepancy between left to right side for a specific motion like hip internal rotation rarely exceeds 16°. 45,46 In this case, left internal rotation was 60°compared to 20°on the right.…”
Section: Discussionmentioning
confidence: 99%
“…[44][45][46] The normal discrepancy between left to right side for a specific motion like hip internal rotation rarely exceeds 16°. 45,46 In this case, left internal rotation was 60°compared to 20°on the right. Also, hip flexion was 130°on the left compared to 90°on the right.…”
Section: Discussionmentioning
confidence: 99%